2015
DOI: 10.1111/bij.12545
|View full text |Cite
|
Sign up to set email alerts
|

Temperature influences host instar selection in an aphid parasitoid: support for the relative fitness rule

Abstract: The relative fitness rule states that parasitoid females should adopt risk‐prone reproductive behaviours when expecting low reproductive success. Temperature influences the reproductive success of insects by affecting their basal metabolic rate during development, their egg load at emergence, and their life expectancy as adults. Using an aphid–parasitoid model system, we investigated the influence of developmental and adult temperature on the risk‐sensitive decision‐making of females. We considered the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 41 publications
(58 reference statements)
1
29
1
Order By: Relevance
“…Alternatively, concentrating reproduction in early life could still be advantageous for small individuals even if females of all sizes experience the same high level of environmental stochasticity. In accordance with the ‘relative fitness rule’ (Giraldeau & Boivin, ; Moiroux, Boivin & Brodeur, ), being able to maximally exploit the first patch of hosts encountered could increase the fitness of small individuals relative to larger individuals, in the event that there is a stochastic mortality event that affects the entire population. Small individuals are advantaged by such stochastic mortality because their loss of future fitness gain (proportional offspring contribution to the next generation) is lower relative to that of large individuals (Giraldeau & Boivin, ).…”
Section: Discussionmentioning
confidence: 95%
“…Alternatively, concentrating reproduction in early life could still be advantageous for small individuals even if females of all sizes experience the same high level of environmental stochasticity. In accordance with the ‘relative fitness rule’ (Giraldeau & Boivin, ; Moiroux, Boivin & Brodeur, ), being able to maximally exploit the first patch of hosts encountered could increase the fitness of small individuals relative to larger individuals, in the event that there is a stochastic mortality event that affects the entire population. Small individuals are advantaged by such stochastic mortality because their loss of future fitness gain (proportional offspring contribution to the next generation) is lower relative to that of large individuals (Giraldeau & Boivin, ).…”
Section: Discussionmentioning
confidence: 95%
“…For example, insect parasitoids that are smaller as a result of developing at higher temperatures may have altered fecundity, basal metabolic rates, and life expectancy, changing the efficiency with which they interact with hosts and exploit host patches (Colinet et al 2007;LeLann et al 2011). Due to their smaller size, warm-developing parasitoids tend to be less capable of subduing larger hosts (LeLann et al 2011;Wu et al 2011;Moiroux et al 2015) and may adopt more risk-prone behaviour (Moiroux et al 2015), possibly representing adaptive behavioural plasticity in response to developmental temperature-induced size variation. Oviposition rate was higher, and patch residence time and host handling time were shorter in females reared at low temperature than females reared at high temperature when foraging at a common temperature.…”
Section: Long-term Kinetic Effectsmentioning
confidence: 99%
“…Modifications of the parasitoid guild could also be due to shifts in competition for hosts following the addition of new species. Indeed, female parasitoids show seasonal variations in foraging behavior (Roitberg et al, 1992) and can adapt their foraging strategies to competition or host-patch quality (Barrette et al, 2010;Le Lann et al, 2008;Moiroux et al, 2015;Outreman et al, 2005). In winter, it has been demonstrated that female parasitoids adopt generalist strategies due to shortage of optimal hosts, leading to high competition, whereas spring parasitoids usually display specialist strategies by selecting optimal host species (Eoche-Bosy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%